1977
DOI: 10.1073/pnas.74.7.2715
|View full text |Cite
|
Sign up to set email alerts
|

Expression of petite mitochondrial DNA in vivo: zygotic gene rescue.

Abstract: A protocol is introduced for probing the organization and regulation of expression of the yeast mitochondrial genome, termed "zygotic gene rescue." The procedure is based on the notion that genes retained on mitochondrial DNA of petites can be expressed in zygotes of a cross between petite and wild type. To test the validity of this notion, we have taken advantage of our ability to discriminate, by mobility differences on sodium dodecyl sulfate/polyacrylamide gels, different forms of the product of alleles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Map of Petite Al 7-10 and Sequencing Strategy The mitochondrial DNA (mtDNA) of petite Al 7-10 was shown by Vincent et al (1980) to be a 5.3 kb headto-tail repeat. From transmission analysis and zygotic gene-rescue analysis (Strausberg and Butow, 1977;Vincent et al, 1980;Lopez et al, 19811, we know that Al 7-l 0 mtDNA contains the entire varl determinant region located within a 2.7 kb fragment corresponding to Hint II band 10 of the wild-type genome. The restriction map of Al 7-l 0 mtDNA has been extended with ten additional enzymes to show fine structure (Hudspeth et al, manuscript in preparation), and a summary of that map for Hint II band 10 is shown in Figure 1.…”
Section: Restrictionmentioning
confidence: 99%
“…Map of Petite Al 7-10 and Sequencing Strategy The mitochondrial DNA (mtDNA) of petite Al 7-10 was shown by Vincent et al (1980) to be a 5.3 kb headto-tail repeat. From transmission analysis and zygotic gene-rescue analysis (Strausberg and Butow, 1977;Vincent et al, 1980;Lopez et al, 19811, we know that Al 7-l 0 mtDNA contains the entire varl determinant region located within a 2.7 kb fragment corresponding to Hint II band 10 of the wild-type genome. The restriction map of Al 7-l 0 mtDNA has been extended with ten additional enzymes to show fine structure (Hudspeth et al, manuscript in preparation), and a summary of that map for Hint II band 10 is shown in Figure 1.…”
Section: Restrictionmentioning
confidence: 99%
“…To avoid this problem, we tested transient expression of cytochrome b in zygotes with the desired genotype generated by mass mating, an approach developed by Strausberg and Butow (21 Genetics: Costanzo and Fox to wild-type PET494 by using the cloned gene, and the resulting transformant, MCC67, was also mass-mated with the double mutant, MSUcbsl-2 strain MCC64. Mitochondrial translation products of the mass-mated cells were radioactively labeled and inspected for the presence of cytochrome b (Fig.…”
Section: Selection and Characterization Of Mitochondrial Mutationsmentioning
confidence: 99%
“…A 4:1 ratio of mated to unmated cells was achieved. Mitochondrial translation products of mated or haploid cells were radioactively labeled and subjected to electrophoresis as described (9,21).…”
mentioning
confidence: 99%
“…To determine whether there would be a correlation between an increased expression of mitochondrial catalytic respiratory chain subunits and mitochondrial respiratory activity by E 2 , we measured the succinate‐stimulated respiration of isolated intact mitochondria from E 2 ‐treated in comparison to control astrocytes from cortex and mesencephalon. After E 2 treatment, cortical and mesencephalic astrocytes were incubated in NBM for an additional 4 h to allow translation of mRNA transcripts and protein targeting into mitochondria (28, 29). Subsequently, intact mitochondria were isolated from E 2 ‐treated and untreated cortical and mesencephalic astroglial cell cultures.…”
Section: Resultsmentioning
confidence: 99%